MAPPING THE DEGREE OF TECHNOLOGICAL CAPABILITY IN SMALL AND MEDIUM INDUSTRY OF AUTOMOTIVE COMPONENTS - Sella Antesty; Alva Edy Tontowi; Arif Kusumawanto (Master in Systems Engineering, 2020)
The automotive industry is known to increase exports since 2015 and is predicted to continue to grow. To develop the industry, the government is known to issue several schemes, and one of them is in the form of mandatory rules for partnerships with the small and medium industrial sectors. However, there is no industrial, institutional map seen from various aspects, including technology, human resources, information, and organization. This map is essential and useful for stakeholders to develop the industry because it provides more directed assistance.In this study, the small and medium industries for processing metal automotive components in Tegal City are used as mapping objects. The technometric method is used to calculate the level of technology contribution they have. The results of this study indicate that the four aspects covering Technoware, Humanware, Infoware, and Orgaware for small and medium-sized automotive component processing industries in Tegal City are in a reasonable range. For improvement or guidance, production facility technology is the priority. Then proceed to employee competencies, information systems, and organizational management. Mapping should be done regularly every five years or less than five years as an evaluation.